Local expansion of a panmictic lineage of water bloom-forming cyanobacterium Microcystis aeruginosa. - Yuuhiko Tanabe (Public Library of Science (PLoS), 2011)
In previous studies, we have demonstrated that the population structure of the bloom-forming cyanobacterium Microcystis aeruginosa is clonal. Expanded multilocus sequence typing analysis of M. aeruginosa using 412 isolates identified five intraspecific lineages suggested to be panmictic while maintaining overall clonal structure probably due to a reduced recombination rate between lineages. Interestingly, since 2005 most strains belonging to one of these panmictic clusters (group G) have been found in a particular locality (Lake Kasumigaura Basin) in Japan. In this locality, multiple, similar but distinct genotypes of this lineage predominated in the bloom, a pattern that is unprecedented for M. aeruginosa. The population structure underlying blooms associated with this lineage is comparable to epidemics of pathogens. Our results may reveal an expansion of the possible adaptive lineage in a localized aquatic environment, providing us with a unique opportunity to investigate its ecological and biogeographical consequences.